Synovial Hemangioma of the Stifle Joint in a Kangal Dog: english - Dayı, B; Sevimli, A (Journal of the Hellenic Veterinary Medical Society, 2024)
A 10-year-old intact male Kangal dog presented with a mass located in the left stifle joint. The mass was 1.2x0.8x1 cm in size. Hematoxylin-eosin and immunohistochemical staining methods were used for histopathological evaluation. Histopathological examination revealed a significant proliferation in synoviocytes. Also, vascular channels lined with well-differentiated endothelial cells were detected. Immunohistochemically, mild CD31 expression was observed in the endothelial cells of the vascular channels. Actin expression was detected in smooth muscle cells of the vascular channels. In addition, vimentin expression was observed in the stromal connective tissue around blood vessels. Based on these findings, the mass was diagnosed as synovial hemangioma. In this case report, synovial hemangioma is rarely observed in animals has been reported.